Our Results of Hyperbaric Oxygen or Pars Plana Vitrectomy in Central Retinal Artery Obstruction - S. Doğruya; B. T Altınbay; Ö. C. Kayıkçıoğlu; M. Altınışık; E. Kurt; Ö. R. Kayıkçıoğlu (Journal of Investigative Surgery)
Purpose We aimed to present the results of patients with central retinal artery obstruction (CRAO) who underwent 23-G pars plana vitrectomy (PPV) or hyperbaric oxygen therapy (HBOT) following emergency medical therapy.Method The files of 15 patients with acute CRAO were retrospectively reviewed. Comprehensive ophthalmological examinations of the patients were performed. Seven patients received HBOT, and eight patients received PPV following emergency medical treatment. The patient’s demographic characteristics, initial and final visual acuity, intraocular pressure were examined.Results The mean age was 65.2 ± 9.9 years in the hyperbaric oxygen therapy group and 58.7 ± 12.8 years in the PPV group. There was no statistically significant difference between the group receiving HBOT and the group undergoing PPV regarding age, initial visual acuity, final visual acuity, visual gain difference between visual acuity improvements, intraocular pressure, and time lag for treatment initiation (p > 0.05).Conclusion Although some improvement in visual acuity was observed in both treatment groups – particularly in patients who underwent PPV – this change did not reach statistical significance. Therefore, despite timely intervention, the overall visual outcomes in CRAO remain poor.